Combining ability of bread wheat genotypes for yield and yield-related traits under drought-stressed and non-stressed conditions. Issue 2 (15th March 2021) - Semahegn, Yared; Shimelis, Hussein; Laing, Mark; Mathew, Isack
Abstract : Drought is a major cause of reduced yields in dryland wheat production. This study aimed to determine the combining ability effects of selected bread wheat genotypes ( Triticum aestivum L.) for yield and yield-related traits. Eight parental lines were selected and crossed using a half-diallel mating design. The parents and 28 crosses were evaluated at two sites in Ethiopia, representing drought-stressed and non-stressed conditions, using a 6 x 6 simple lattice design. The parental line ETW17302 was the best general combiner for the growth indices: days to heading, days to maturity, grain-filling period, and 1 000-kernel weight, thereby enabling direct selection for improved grain yield under a drought-stressed condition. Parent ETW17377 could also be used for improving grain yield under a drought-stress condition owing to its positive and significant general combining ability effect on grain yield. The families ETW17302 × ETW17377, ETW17396 × ETW17374, and ETW17396 × ETW17385 were the best specific combiners for improving grain yield under the drought-stressed condition. The selected parents and families are desirable genetic resources to enhance yield and yield-related traits under both drought-stressed and non-stressed conditions.